Highly Efficient Decoupled Triple‐Channel OAM Generation with a Single‐Layer Shared Aperture Reflective Metasurface. Issue 3 (1st December 2022) - Jiang, Yuying; Liu, Liangliang; Li, Shuying; Tang, Chunzi; Luo, Zhengzhi; Zhu, Zhengtao; Cao, Yuxiang; Gu, Changqing; Li, Zhuo
Abstract: Metasurface is extensively studied for generating multicharacteristic orbital angular momentum (OAM) beams. However, designing a highly integrated and independent polarization‐frequency multiplexing metasurface for efficient multiscenario OAM‐related applications is still a challenge. Here, a triple‐band single‐layer shared aperture reflective metasurface for triple‐polarization channels independent OAM modulations is proposed. The specific frequency quantitative customization resonance phase and quasi‐static geometric phase are utilized to manipulate the dual‐band (Ku‐ and K‐band) orthogonal linearly polarized (LP) channel and C&X‐band right‐handed circularly polarized (RHCP) channel. An isolation ring is introduced for eliminating the strong coupling between the structurally compatible RHCP and orthogonal‐LP subunits in a shared aperture meta‐atom. It is revealed that the isolation ring not only helps realize efficient multipolarization, multiband, and multimode OAM generation, but also expands the operation bandwidth of the RHCP channel OAM. A proof‐of‐concept prototype of the designed metasurface is constructed to verify the methodology and the experimental results are in excellent agreement with simulations. The proposed independent OAM modulation scheme for extending the functionality of metasurface offers a novel route to realize multipolarization and multiband OAM beams with high isolation, which may have potential applications in OAM‐based multichannel multiplexing communications. Abstract : A triple‐band single‐layer shared aperture reflective metasurface for triple‐polarization channels independent orbital angular momentum (OAM) modulations is proposed. An isolation ring is introduced for eliminating the strong coupling between the quasi‐static right‐handed circularly polarized (RHCP) subunit and the two dual‐band orthogonal‐linearly polarized subunits in a single compatible shared aperture meta‐atom. Additionally, the isolation ring expands the operation bandwidth of the RHCP channel OAM.